Photothermal deflectometry enhanced by total internal reflection enables non-invasive glucose monitoring in human epidermis. Issue 2 (19th November 2014) - Pleitez, M. A.; Hertzberg, O.; Bauer, A.; Seeger, M.; Lieblein, T.; Lilienfeld-Toal, H. v.; Mäntele, W.
Abstract : We present an IR-pump/VIS-probe method for the measurement of ir absorption spectra by means of photothermal deflectometry (ptd) enhanced by total internal reflection (tir). This technique is termed tir-ptd spectroscopy. Abstract : We present TIR-PTD spectroscopy, an IR-pump/VIS-probe method for the measurement of IR absorption spectra by means of photothermal deflectometry (PTD) enhanced by total internal reflection (TIR). It overcomes the limitations of IR spectroscopy for the study of opaque samples and allows molecular fingerprinting of IR-active liquids or solids. Another important advantage of the presented approach over traditional IR spectroscopy methods is the ability to obtain IR information by means of VIS detection, which is generally much cheaper and easier to handle than IR detection. By application of mid-IR TIR-PTD spectroscopy on human skin in vivo, we are demonstrating the correlation between epidermal- and blood-glucose levels on a type 1 diabetic patient.